Seasonal Changes and Age-Related Effects on the Intestinal Microbiota of Captive Chinese Monals (Lophophorus lhuysii) - Lijing Huang; Yanchu Zheng; Shaohua Feng; Bangyuan Wu; Li Chen; Xiaoqin Xu; Bin Wang; Wanhong Li; Caiquan Zhou; Long Zhang (Animals)
The Chinese monal (Lophophorus lhuysii) is a large-sized and vulnerable (VU in IUCN) bird from southwestern China. This study applied 16S rRNA high-throughput sequencing to comprehensively examine the gut microbiota of captive Chinese monals (located in Baoxing, Sichuan, China) across varying seasons and life stages. Dominant bacterial phyla identified included Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria. Significant seasonal and age-associated shifts were observed within specific bacterial groups, particularly marked by seasonal fluctuations in beta diversity. Moreover, linear discriminant analysis effect size (LEfSe) and functional predictions highlighted distinct winter signatures, indicating possible functional shifts in energy metabolism and disease resistance. In mid-aged adults, an expansion of Gamma-Proteobacteria suggested an elevated susceptibility of the gut microbiota of Chinese monals to chronic disorders and microbial imbalance. Putative pathogenic bacteria exhibited increased abundance in spring and summer, likely driven by temperature, host physiological cycles, interspecies interactions, and competition. These findings imply that the diversity, and structure of the gut microbiota in captive Chinese monals are strongly influenced by seasonal and age-related factors. The insights provided here are essential for improving breeding strategies and preventing gastrointestinal diseases in captivity.